Comparison of Modified Early Obstetric Warning Score (MEOWS) and Maternal Early Warning Criteria (MEWC) as Predictor of Morbidity and Mortality of Pregnant Women With COVID-19 in Bantul Hospital - Desti Cahyani, Dinda; Permana, Iman (Rifa'Institute, 2022)
Background: The Indonesian Association of Obstetrics and Gynecology found that 20% of pregnant women died during the pandemic, dominated by cases of pregnant women who were confirmed positive for COVID-19. Maternal mortality reached three times the pre-pandemic level in July 2021. Objective: The purpose of this study was to compare the Modified Early Obstetric Warning Score (MEOWS) and Maternal Early Warning Criteria (MEWC) in predicting maternal morbidity and mortality in women infected with COVID-19. Method: The retrospective cohort method was used in this study of 91 obstetric patients infected with COVID-19 who were hospitalized at the Panembahan Senopati Bantul Regional General Hospital from January 2021 to December 2021. Result and discussion: The results of the calculation of the different tests obtained a p-value of 0.000=0.05 (the p-value is smaller than = 0.05). This means that there is a significant difference between the Modified Early Obstetric Warning Score (MEOWS) and the Maternal Early Warning Criteria (MEWC) in pregnant patients with confirmed COVID-19 at the Bantul Regional General Hospital. MEWC can predict a maternal mortality rate of 60.67%. Meanwhile, MEOWS can only predict maternal morbidity and mortality in 37.08% of COVID-19-positive pregnant patients. Conclusions: The Maternal Early Warning Criteria (MEWC) is better than the Modified Early Obstetric Warning Score (MEOWS) in predicting morbidity and mortality in pregnant patients with confirmed COVID-19